Iowa Ornithologists' Union, field report compiled data, Snowy Owl, 1979-1983 - Iowa Ornithologists' Unionet al (1979)
Compilation of sightings data for the Snowy Owl submitted to the Iowa Ornithologists' Union by members between the years 1979-1983. The document also includes the name of the observer, date, and location. Epson - sheet feed